Respuesta :

Answer:

Step-by-step explanation:

Part A

The first thing you have to do is develop a formula for the line.

It goes through (-2,3)

It has a y intercept of (0,-1)

So far what you know is

y = mx - 1

x = - 2

y = 3

3 = m(-2) - 1                  Add 1 to both sides

3 + 1 = (-2)*m

4 = - 2*m                      Divide by - 2

4/-2 = m

m = - 2

The equation of the line is y = -2x - 1

Instead of y, we can use f(x)

f(x) = -2x - 1

Finally we can solve this part of the question.

f(1) = - 2(1) - 1

f(1) = -2 - 1

f(1) = - 3

Part B

f(x) = 5

y = 5

5 = -2x - 1           Add 1 to both sides

5+1 = - 2x           Divide by - 2

6 / -2 = -2x/-2

-3 = x